Other-regarding behaviour: Testing guilt- and reciprocity-based models - Tobias Regner; Nicole S. Harth (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
Intentions-based models of social preferences use the framework of psychological games and incorporate higher order beliefs and actions into the utility function. We test the robustness of two types of intentions-based models (guilt aversion and reciprocity). In addition to incentivised elicitation of first- and second-order action beliefs, we assess participants' sensitivity to feel guilt, and their attitude towards acting reciprocal. The data confirm the predictions of intentions-based models. Both second-order beliefs and the weighting factor that depends on a participant's sensitivity to guilt/reciprocity are relevant for the decisions taken. Second-order beliefs appear to have an inverse U-shaped effect on the amount returned.
Keywords: C91; D03; D84; 330; social preferences; other-regarding behaviour; experiments; trust game; guilt aversion; beliefs; psychological game theory; emotions; Soziale Beziehungen; Soziale Wohlfahrtsfunktion; Test; Vertrauen; Austauschtheorie (Soziologie); Emotion